Pengaruh Experiential Marketing terhadap Kepercayaan Masyarakat melalui Kepuasan Layanan pada Program Bimbingan Perkawinan di KUA Sunggal - Nur Fatiha Utami Nasution; Nanda Fitria Aulanda; Nina Annisa (STAIN MAJENE, 2026)
This study analyzed the empirical influence of experiential marketing assessed through sense (X1), feel (X2), think (X3), act (X4), and relate (X5) on public trust (Y) mediated by service satisfaction (Z) among participants of the Marriage Guidance Program (Bimwin) at the Office of Religious Affairs (KUA) in Sunggal District. The population in this study comprises participants who completed the program, yielding a valid primary sample size of 185 respondents obtained through purposive sampling, complemented by secondary data from semi-structured interviews with KUA management. The research was conducted from January to March 2026. This study uses quantitative data processed by the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis method using SmartPLS software. The results of the study show that experiential marketing, which consists of sense, feel, think, act, and relate dimensions, has a positive and significant effect on both service satisfaction and public trust. Furthermore, service satisfaction is also found to have a positive and significant effect on public trust. Concurrently, the mediation analysis verified that service satisfaction successfully acts as a potent intervening bridge that mediates the influence of experiential marketing on public trust. The managerial implication of this study is the need for KUA Sunggal to continue to improve the experiential marketing strategy, especially by transforming rigid administrative procedures into humanistic, active-learning experiences, optimizing interaction quality, and maintaining a comfortable environment. This is important to build service satisfaction and ultimately improve the public trust in religious public dawah institutions